Thermal Stability Analysis of Cyperus Rotundus L Reinforced HDPE Composite in Polymer Composite Roof Tiles - Muhammad Fakhri Hamzah; Budhi Martana; Fahrudin Ulwani; Armansyah; Fitri Wahyuni (International Journal of Marine Engineering Innovation and Research, 2024)
One of the materials that may be utilized in polymer matrix composites is high-density polyethylene (HDPE) plastic. Large amounts of HDPE plastic waste can harm the environment. Therefore, a solution is needed to overcome this problem. One solution to reduce plastic waste is to utilise it into polymer composite roof tiles. Roof tile surfaces are subjected to the greatest amount of solar heat radiation. This study aims to analyze the effect of variations in the composition of HDPE and teki grass on the value of solar radiation heat transfer and the value of thermal stability in polymer composite roof tiles. This research uses an experimental method by composites HDPE and teki grass with variations in the weight of teki grass used by 0%, 10%, 15%, and 20%. The results show that 20% teki grass composition in the composite produces low radiant heat compared to 0% teki grass composition which tends to be higher. according to the findings of the thermal stability test., The maximum thermal stability was seen in the composite with 0% fiber composition. While the most unstable composite is at 20% fiber composition with a 5% weight loss at 164.47oC and 10% at 278.27oC.